Identification of CDC42 Effectors Operating in FGD1-Dependent Trafficking at the Golgi - Egorov, Mikhail; Polishchuk, Roman (Frontiers in Cell and Developmental Biology, 2019)
Loss of function mutations in the FGD1 gene cause a rare X-linked disease, faciogenital dysplasia (FGDY, also known as Aarskog-Skott syndrome), which is associated with bone and urogenital abnormalities. The FGD1 gene encodes à CDC42-specific guanine nucleotide exchange factor. The mutations are frequently located in the DH module of FGD1 preventing its transformation to the active form. We previously reported that Golgi-associated FGD1 regulates post-Golgi transport of some conventional and bone-specific proteins in a CDC42-dependent manner. However, the downstream targets of FGD1/CDC42 signaling that operate to support transport from the Golgi remain elusive. Here, we demonstrate that Golgi-localized CDC42 effectors might be involved in FGD1-mediated post-Golgi transport, probably through coordination of Golgi membrane and cytoskeleton dynamics. Overexpression of effector-specific CDC42 mutants (exhibiting preferential affinities for PAK1, IQGAP1, N-WASP, or PAR6) only partially rescue membrane trafficking in FGD1-deficient cells, indicating that the orchestrated activities of several downstream targets of CDC42 are required to support FGD1-mediated export from the Golgi. Our findings provide new insights into understanding the molecular mechanisms behind FGD1/CDC42-dependent transport events and uncover new targets whose potential might be explored for correction of membrane trafficking in FGDY.